ANALISIS KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR SEBELUM DAN SESUDAH MERGER DAN AKUISISI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014 - 2015 - -, Toni Hariyadi (EKONOMIA, 2019)
The purpose of this study is to prove that there are differences in the financial performance before and after mergers and acquisitions of manufacturing acquirers listed in the Indonesia Stock Exchange during the period 2014-2015.The research question of this study was: â€œAre there significant differences in the financial performance of the acquirers listed in Indonesia Stock Exchange before and after merger and acquisition in 2014-2015?â€ The theoretical bases used in this study are management, financial management, financial performance, and t-test. The hypothesis of the study was: â€œThere are significant differences in financial performance as measured by Total Asset Turnover, Net Profit Margin, and Return on Assets of the manufacturing companies listed in Indonesia Stock Exchange before and after merger and acquisition in 2014-2015.â€Analysis and hypothesis testing instrument used in this study are financial statements ratio, which includes the Total Asset Turnover, Net Profit Margin and Return on Assets, and Paired sample t-test.The analysis revealed that in the three companies listed in the Indonesia Stock Exchange and conducting mergers and acquisitions in 2014-2015, the ratio of financial statements that include the Total Asset Turnover, Net Profit Margin, and Return on Assets decreased as the increased number of sales and profits were not in accordance with the increase in the total assets. The results of Paired sample t-test to examine the level of significance of the differences in financial performance after merger and acquisitions showed that TAT was not significant (t-value<t-table; 2.223<4.303), NPM was not significant either (t-value<t-table; 1.717<4.303) while RoA was significant (t-value>t-table; 4.346>4.303).The findings showed that the financial performance of the manufacturing companies listed in Indonesia Stock Exchange in 2014-2015 before and after the merger and acquisition did not differ significantly. Thus, the hypothesis is rejected.